IDENTIFICATION AND EVALUATION OF FIBER HYDROLYTIC ENZYMES IN THE EXTRACT OF TERMITES (Glyptotermes montanus) FOR POULTRY FEED APPLICATION - Tresnawati Purwadari; Pius P. Ketaren; Arnold P. Sinurat; Irawan Sutikno (Indonesian Agency for Agricultural Research and Development, 2003)
Foot rot disease of black pepper caused by Phytophthora capsici had been reported in Batangas and Laguna, Philippines. The plant was recovered following the application of crop residue (organic substrate) and intercropping with other crops. This study was aimed to isolate, identify, and determine the soil mycoflora from the rhizosphere of black pepper grown on various cropping patterns in Batangas and Laguna. Antagonistic activity of mycoflora isolates was tested against P. capsici using dual culture technique. The result showed that 149 colonies of soil mycoflora isolated were belonging to 14 genera; three of them, i.e. Penicillium, Paecilomyces and Aspergillus, were the most dominant. All of the mycoflora isolates were able to inhibit the growth of the pathogen. Eighteen of them were the most promising antagonists, based on their inhibition growth of more than 60%. It is suggested that antagonistic mechanism of Mucor isolate (1001), Trichoderma (125, 170, 171, 179, 180, 181), Gliocladium (109), Cunninghamella (165, 168), Mortierella (177), and Aspergillus (106) was space competitor (competition for nutrient) since they rapidly overgrew the pathogen. Aspergillus (67, 79, 81, 83, 108, and 202) isolates inhibited the pathogen apparently by producing antibiotic, whereas Trichoderma (125, 170, 171, 179, 180, and 181) isolates were able to penetrate the hyphae of the pathogen. The organic matter percentage in the soil was significantly correlated with the number of antagonistic mycoflora in rhizosphere (R2 = 0.1094), but the cropping pattern wPoultry are not able to digest fiber in the diet. Hydrolytic enzymes including cellulases and hemicellulases have been used as poultry feed supplement. Termites (Glyptotermes montanus) have the ability to digest wood that contains high fiber. The purpose of this experiment was to identify the cellulase and hemicellulase of termite extract. The hydrolytic (saccharification) activity of the termite extract on feedstuffs was then evaluated. It contained high endo-β-D-1,4-glucanase (CMCase) activity, but the activities of avicelase, β-D-1,4-mannanase, β- D-1,4-xylanase, and β-D-1,4-glucosidase were very low. The activities of the enzymes were higher in the fresh extract than those extracted after drying at 40oC with blower oven. CMCase (as cellulase), β-D-1,4-mannanase (as hemicellulase), and β-D- 1,4-glucosidase (as glycosidase) were reevaluated further to determine the optimum pH and temperatures for maximum activities. The optimum pH for CMCase, β-D-1,4-mannanase, and β-D-1,4-glucosidase were 6.2, 5.0, and 5.8 respectively, while the optimum temperatures were 45-50oC, 50-55oC, and 42-45oC, respectively. The enzyme mixture or cocktail was more appropriate in digesting feedstuffs with high lignocellulose (fiber) such as rice bran and pollard than feedstuffs with more soluble starch such as soybean and corn meals. The extracted enzyme could be immobilized with pollard, but CMCase recovery was low (28.6%), while β-D-1,4-mannanase and β-D-1,4-glucosidase recoveries were 89.2% and 272.9%, respectively. Termite extract contained enzyme cocktails of lignocellulases that potentially be used as feed supplement. However, its use is limited by its low activity.as negatively correlated. This study suggests that organic matter increased antagonistic mycoflora in black pepper rhizosphere, which will reduce severity of the disease.